Gender differences in trusting strangers: Role of the target's gender. Issue 2 (12th January 2016) - Zhao, Na; Zhang, Jianxin
Abstract: Previous findings on gender differences in the behaviors of individuals, including trusting behaviors, are inconsistent. A criticism is that these studies neglect contextual factors. The present study aims to examine how the target's gender, as a primary context factor, influences the trusting behavior of individuals in one survey and two experimental situations. Results indicate that people tend to trust strangers of the opposite gender more than those of the same gender in mixed‐gender situations. Furthermore, females trust females much more than males trust males. The results help people understand that when talking about gender differences in interpersonal situations, the gender identity of target persons should be considered. These findings are somewhat in conflict with those of previous studies conducted in Western cultures, and suggest that culture should also be explored in future studies on gender differences in interpersonal relationships.